O PERFIL DAS INOVAÇÕES NO CONTEXTO DO DESENVOLVIMENTO TERRITORIAL DE SÃO PAULO, RIO DE JANEIRO, MINAS GERAIS E PARANÁ - 2002 A 2017 - SANTOS, LUCAS CORDEIRO DOS (2020)
Technological innovations are essential for the territorial development context. The Fourth Industrial Revolution has boosted the automation process, whose socioeconomic impacts lead to the necessity of new perspectives. Territorial development and universities engagement were boosted by the Law of Innovation nº 10.973 from 2004, resulting in an approach between public and private agents. Considering these factors, this study aims at explaining the profile of innovations in the territorial development context of São Paulo (SP), Rio de Janeiro (RJ), Minas Gerais (MG), and Paraná (PR) between the years 2002 and 2017. To do so, the quali-quantitative method contemplated five stages: 1) Characterization of the states of SP, RJ, MG, and PR. With socioeconomic data, public higher education institutions enrollment data, and profile of production and exportation; 2) Technological prospection of public universities from SP, RJ, MG, and PR, using the e-MEC platform and the Orbit system; 3) Explanation, through data and graphs, of the patents deposited by public universities from SP, RJ, MG, and PR; 4) Analysis of the obtained results, based on the amount of gathered data, enumerating the areas of the deposited patents, according to International Patent Classification (IPC) and Technology Domains, and also the patents’ legal Status; 5) Systematization of results in a strategic perspective of Innovative Territorial Development. The results presented that the states of SP, RJ, MG, and PR concentrate expressive relevance in the national scenario, representing 57% of the country’s GPD, 45% of the national population, and territorial extension of 12%. Regarding exportation, primary products stand out, such as Raw Sugar with concentration of 14,8% in SP, Petroleum with 60,5% in RJ, Iron Ore with 34,2% in MG, and Soybean with 22,9% in PR. Employment structure in these four states is based on the tertiary sector with Commerce concentrating 20,23% in São Paulo, 20,1% in Rio de Janeiro, 20,83% in Minas Gerais, and 21,42% in Paraná, therefore characterizing low-tech sectors as the exportation and employment profile of these states. Considering ICP, the profile of patents deposited by public universities from the states of SP, RJ, MG, and PR, is represented primarily by Section A – Human Necessities. Among the ten most deposited codes, two with the highest concentration stood out: A61P-035/00 - Antineoplastic agents (20,26%), and A61P-031/04 – Antibiotic agents (12,44%). Regarding technology domains, Chemistry predominates with 78,7% of the deposited patents prospected in this study. The most deposited technology subdomain is Pharmaceutics, with 15,37%. It is also worth pointing out that the results indicated a percentage of 53,41% of patents being analyzed, demonstrating the necessity for the concession process to become more agile as in developed countries. Based on the profile presented, the strategic perspective for territorial development, in accordance with the Fourth Industrial Revolution scenario, is the diversification and development of patents in the information science area, on segments such as: artificial intelligence, internet of things, and 3D printing, aiming the adaptation to the evident transformative scenario. However, it is necessary that Government, Universities, and Companies work viii together, so that the innovation system becomes effective through long-term public policies.